Step
*
2
1
1
1
1
2
of Lemma
equipollent-product
1. n : ℤ
2. n ≠ 0
3. [%1] : 0 < n
4. ∀f:ℕn - 1 ⟶ ℕ. i:ℕn - 1 ⟶ ℕf[i] ~ ℕΠ(f[i] | i < n - 1)
5. f : ℕn ⟶ ℕ
6. i:ℕn - 1 ⟶ ℕf[i] ~ ℕΠ(f[i] | i < n - 1)
7. b : i:ℕn - 1 ⟶ ℕf[i] × ℕf[n - 1]
⊢ ∃a:i:ℕn ⟶ ℕf[i]. (<a, a (n - 1)> = b ∈ (i:ℕn - 1 ⟶ ℕf[i] × ℕf[n - 1]))
BY
{ ((D (-1) THEN With ⌜λi.if (i =z n - 1) then b2 else b1 i fi ⌝ (D 0)⋅) THEN Reduce 0 THEN Auto) }
1
1. n : ℤ
2. n ≠ 0
3. 0 < n
4. ∀f:ℕn - 1 ⟶ ℕ. i:ℕn - 1 ⟶ ℕf[i] ~ ℕΠ(f[i] | i < n - 1)
5. f : ℕn ⟶ ℕ
6. i:ℕn - 1 ⟶ ℕf[i] ~ ℕΠ(f[i] | i < n - 1)
7. b1 : i:ℕn - 1 ⟶ ℕf[i]
8. b2 : ℕf[n - 1]
⊢ <λi.if (i =z n - 1) then b2 else b1 i fi , if (n - 1 =z n - 1) then b2 else b1 (n - 1) fi >
= <b1, b2>
∈ (i:ℕn - 1 ⟶ ℕf[i] × ℕf[n - 1])
Latex:
Latex:
1.  n  :  \mBbbZ{}
2.  n  \mneq{}  0
3.  [\%1]  :  0  <  n
4.  \mforall{}f:\mBbbN{}n  -  1  {}\mrightarrow{}  \mBbbN{}.  i:\mBbbN{}n  -  1  {}\mrightarrow{}  \mBbbN{}f[i]  \msim{}  \mBbbN{}\mPi{}(f[i]  |  i  <  n  -  1)
5.  f  :  \mBbbN{}n  {}\mrightarrow{}  \mBbbN{}
6.  i:\mBbbN{}n  -  1  {}\mrightarrow{}  \mBbbN{}f[i]  \msim{}  \mBbbN{}\mPi{}(f[i]  |  i  <  n  -  1)
7.  b  :  i:\mBbbN{}n  -  1  {}\mrightarrow{}  \mBbbN{}f[i]  \mtimes{}  \mBbbN{}f[n  -  1]
\mvdash{}  \mexists{}a:i:\mBbbN{}n  {}\mrightarrow{}  \mBbbN{}f[i].  (<a,  a  (n  -  1)>  =  b)
By
Latex:
((D  (-1)  THEN  With  \mkleeneopen{}\mlambda{}i.if  (i  =\msubz{}  n  -  1)  then  b2  else  b1  i  fi  \mkleeneclose{}  (D  0)\mcdot{})  THEN  Reduce  0  THEN  Auto)
Home
Index